2001
DOI: 10.1109/5.929650
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of high-speed interconnects

Abstract: With the rapid developments in very large-scale integration (VLSI) technology, design and computer-aided design (CAD) techniques, at both the chip and package level, the operating frequencies are fast reaching the vicinity of gigahertz and switching times are getting to the subnanosecond levels. The ever increasing quest for high-speed applications is placing higher demands on interconnect performance and highlighted the previously negligible effects of interconnects, such as ringing, signal delay, distortio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
377
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 588 publications
(379 citation statements)
references
References 143 publications
(215 reference statements)
0
377
0
2
Order By: Relevance
“…Therefore proper selection of multiple expansion points is important. Previous studies on multiple-point expansion are found in [1,12,13,20,26,29]. In [26], the expansion points are chosen such that the reduced-order model is locally optimal.…”
Section: For Moment-matching Methods the Matrices W V Are Construcmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore proper selection of multiple expansion points is important. Previous studies on multiple-point expansion are found in [1,12,13,20,26,29]. In [26], the expansion points are chosen such that the reduced-order model is locally optimal.…”
Section: For Moment-matching Methods the Matrices W V Are Construcmentioning
confidence: 99%
“…In [26], the expansion points are chosen such that the reduced-order model is locally optimal. A binary search is used in [1,12,20] for adaptive, but heuristic selection of the expansion points. In Section 7.2, we readdress the problem of selecting multiple expansion points by using the global a posteriori error bounds proposed in Section 3 and Section 4.…”
Section: For Moment-matching Methods the Matrices W V Are Construcmentioning
confidence: 99%
“…Moment-Matching Methods [6][7] can be used to derive a first-order network with effective lumped element parameters for voltage and current mode signaling. It is well understood that a lumped, linear, time-invariant circuit such as that of a generalized distributed RC line shown in Figure 1, can be conveniently expressed in terms of state equations by using the modified nodal admittance matrix (MNA) representation [8] [9].…”
Section: Mna For Closed Form Derivationmentioning
confidence: 99%
“…Thus the distributed transmission line can be effectively modeled by the lumped element resistance and capacitance given in (7)(8). The generalized effective lumped element model is shown in Figure 1(b).…”
Section: Effective Resistance and Capacitancementioning
confidence: 99%
“…For practical designs, the nonuniform interconnects are often used to optimize the circuit performance. Many researches have focused on establishing distributed line models for simulations [1,2,3,5,6,10,11,13]. However, it seems that no suitable model of nonuniform distributed lines has been developed for efficiently analyzing noises.…”
Section: Introductionmentioning
confidence: 99%